Estrus Induction with Exogenous Melatonin in Anestrus Pubertal Jaffarabadi Buffalo Heifers during Summer Season - Ramoliya, Urvashi B; Vijyeta, Hardipsinh P; Padodara, Ramesh J; Vala, Karshan B; Vadalia, Jignesh V; Nandaniya, Nirbhay R (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present study evaluated the effect of exogenous melatonin on ovarian follicular dynamics, hormonal profile, oxidative stress, and conception rate in pubertal Jaffarabadi buffalo heifers during the summer season. Twelve buffalo heifers (32-36 months; 300-350 kg) were randomly divided into two equal groups: Control (Group I; corn oil 1 mL/50 kg s/c) and Melatonin-treated (Group II; melatonin 18 mg/50 kg b.wt. in corn oil s/c). Ovarian activity was monitored using ultrasonography, and blood samples were analyzed for melatonin, progesterone, lipid peroxidation (LPO), and total antioxidant capacity (TAC). Melatonin significantly (p<0.05) enhanced follicular recruitment and follicle diameter, reduced oxidative stress, increased TAC, and improved estrus induction and conception rate. The study demonstrates melatonin’s beneficial role in alleviating heat stress-induced reproductive suppression and improving fertility in buffalo heifers.